IMPROVING MATHEMATICS LEARNING OUTCOMES ON FRACTION MATERIAL THROUGH FRACTION CARD MEDIA IN SECOND GRADE STUDENTS OF NAIKOTEN 2 ELEMENTARY SCHOOL - kulle, Susan kulle susan (Universitas Nusa Cendana, 2025)
This research uses classroom action research procedures aims to improve the learning outcomes of Mathematics on fraction through Fraction Card media for class II students of Naikoten 2 Elementary School. The results of the study were obtained from classroom actions in cycle I and classroom actions in cycle II. The results of this study were seen from the results of tests and non-tests. The test results were in the form of student learning scores at the end of each cycle, namely cycles I and II. The results were then analyzed and used as a benchmark for the success of each cycle. While the non-test results were in the form of data on teacher and student learning activities during learning obtained through observation activitiesIn cycle I, the percentage of student learning completion is still very low, which is 60%. However, cycle I is still considered unsuccessful, so it is necessary to implement cycle II. In the implementation of cycle II, it is known that there is an increase in Mathematics learning outcomes in fraction material, with a very good percentage of completion, which is 81.670%. The increase in student achievement results can be concluded that Mathematics learning in fraction material using Fraction Card media for class II students of Naikoten 2 Elementary School has been successful. However, in every learning process, it must still be supported by activities-activities that can improve student learning activities in class, such as appreciation, motivation and reinforcement to students to keep studying hard.